Partial Differential Equations in Ecology 80 Years and Counting - Petrovskii, Sergei (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Partial differential equations (PDEs) have been used in theoretical ecology research for more than eighty years. Nowadays, along with a variety of different mathematical techniques, they remain as an efficient, widely used modelling framework; as a matter of fact, the range of PDE applications has even become broader. This volume presents a collection of case studies where applications range from bacterial systems to population dynamics of human riots.